Populus nigra. EUFORGEN Genetic Conservation Network - de Vries, S. M.G. (Forest Systems, 2000)
Populus nigra L. is a tree of social and economic importance. It is a unique pioneer species of riparian ecosystems which contributes to the natural control of flooding and water quality, and which is characterised by a high level of diversity of the fauna and flora. P. nigra has direct economic values as supplier of raw materials for industries and is also important as a crossing parent in the production of healthy and fast growing Populus x euramericana hybrids. Its current rarity is due to the loss of its natural habitat due to drainage of rivers and management of riverbanks. It is not known if the genetic diversity of the species has been reduced as a consequence. Another threat to the gene pool might come from the possible interspecific hybridisation. One of the networks is devoted to Populus nigra, the European Black Poplar and one of the aims of the network is to develop appropriate conservation strategies for the species concerned. The Network has developed some activities on dynamic and static genetic conservation, but it is necessary better knowledge to face to genetic conservation at long term. The low level of information about genetic diversity in P. nigra is one of the causes to develop a European project where some studies are being done to establish a long term conservation methodology.